Youth Strategies in the Face of Climate and Educational Vulnerability - Roa González, Iliana Viridiana (Southern perspective / Perspectiva austral, 2024)
Introduction: The study analyzed the risk and vulnerability in the educational trajectory of indigenous youth as they progressed to postgraduate studies. It focused on students from Intercultural Universities and assessed the social, economic, and cultural conditions that influenced their academic development. The research explored the accumulation of disadvantages throughout their education and how transversal factors such as gender, age, and ethnicity impacted their access to and retention in higher education.Development: The analysis was based on semi-structured interviews with postgraduate students from various public universities in Mexico City. It was identified that educational vulnerability was not only a result of structural conditions but also of material and symbolic inequalities. The study examined educational segmentation and the creation of Intercultural Universities as a governmental strategy to include marginalized populations, although it also revealed that these institutions perpetuated institutional differences. Additionally, the impact of the COVID-19 pandemic was addressed, which amplified inequalities and forced indigenous students to develop strategies to cope with distance education, such as using community networks and strengthening digital literacy.Conclusion: The study concluded that the educational vulnerability of indigenous youth was exacerbated by the pandemic, highlighting structural inequality in access to education. However, it emphasized their resilience and the strategies they implemented to mitigate adverse effects. The denaturalization of disasters helped understand the intersection of social, economic, and political factors in the education of vulnerable populations.